Desmoid Fibromatosis in Pediatric Patients: Management Based on a Retrospective Analysis of 59 Patients and a Review of the Literature. (5th August 2012) - Oudot, Caroline; Orbach, Daniel; Minard-Colin, Véronique; Michon, Jean; Mary, Pierre; Glorion, Christophe; Helfre, Sylvie; Habrand, Jean-Louis; Oberlin, Odile
Abstract : Background . Only limited data are available concerning desmoid tumor in children. Methods . Fifty-nine children and adolescents with desmoid tumor treated in 2 French cancer centers with a very long followup were retrospectively reviewed. Results . Median age was 6 years (range, 0–15). Tumors mainly involved the limbs (42%). Five cases occurred in a context of genetic disorder. Surgery was first-line treatment in 80% of cases. Resection was microscopically complete in 3 patients (pts), with a microscopic residue in 19 pts and a macroscopic residue in 35 cases. Various adjuvant therapies were used. Overall response to all systemic therapies was 33%. Thirty-eight patients developed one or more recurrences or progressions. After a median followup of 8.5 years, 34 patients were alive in complete remission (CR), including 16 first CR. Seven patients died, 6 from refractory disease and 1 from colorectal carcinoma in a genetic context. Ten-year progression-free survival (PFS) and overall survival were 31% and 88%, respectively. In univariate analysis, age less than 10 years and head-neck site were favorable prognostic factors for PFS. Conclusions . When surgery is required, surgical margins must be negative. Low-dose chemotherapy can be proposed as adjuvant therapy. Prospective trials must be developed to evaluate long-term response and side effects. Erratum to "Desmoid Fibromatosis in Pediatric Patients: Management Based on a Retrospective Analysis of 59 Patients and a Review of the Literature" dx.doi.org/10.1155/2013/757915